Cholesterol Depletion Regulates Axonal Growth and Enhances Central and Peripheral Nerve Regeneration - Roselló-Busquets, Cristina; de la Oliva, Natalia; Martínez-Mármol, Ramón; Hernaiz-Llorens, Marc; Pascual, Marta; Muhaisen, Ashraf; Navarro, Xavier; del Valle, Jaume; Soriano, Eduardo (Frontiers in Cellular Neuroscience, 2019)
Axonal growth during normal development and axonal regeneration rely on the action of many receptor signaling systems and complexes, most of them located in specialized raft membrane microdomains with a precise lipid composition. Cholesterol is a component of membrane rafts and the integrity of these structures depends on the concentrations present of this compound. Here we explored the effect of cholesterol depletion in both developing neurons and regenerating axons. First, we show that cholesterol depletion in vitro in developing neurons from the central and peripheral nervous systems increases the size of growth cones, the density of filopodium-like structures and the number of neurite branching points. Next, we demonstrate that cholesterol depletion enhances axonal regeneration after axotomy in vitro both in a microfluidic system using dissociated hippocampal neurons and in a slice-coculture organotypic model of axotomy and regeneration. Finally, using axotomy experiments in the sciatic nerve, we also show that cholesterol depletion favors axonal regeneration in vivo. Importantly, the enhanced regeneration observed in peripheral axons also correlated with earlier electrophysiological responses, thereby indicating functional recovery following the regeneration. Taken together, our results suggest that cholesterol depletion per se is able to promote axonal growth in developing axons and to increase axonal regeneration in vitro and in vivo both in the central and peripheral nervous systems.